1998
DOI: 10.1002/(sici)1098-2353(1998)11:5<327::aid-ca6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Classification of communications between the musculocutaneous and median nerves

Abstract: In 16 out of 79 cadavers 22 communications were found between the musculocutaneous and median nerves. In six subjects they were present bilaterally. There were three types, based on the sites of communication. Type I: The communication was proximal to the entrance of the musculocutaneous nerve into coracobrachialis (9/22); Type II: The communication was distal to the muscle (10/22); Type III: The nerve as well as the communicating branch did not pierce the muscle (3/22). Bilateral communications were not neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 6 publications
3
85
0
3
Order By: Relevance
“…Satyanarayana et al (2008) [9] found a four rooted median nerve with three lateral and one medial root. Venieratos et al [10] reported a communicating branch between musculcutaneous nerve and median nerve, this branch after originating from muculocutaneous nerve procceeds downwards and medially to join the median nerve in the lower third of arm. These workers [4], [6], [8] reported that extra roots of median nerve were present unilaterally.…”
Section: Discussionmentioning
confidence: 98%
“…Satyanarayana et al (2008) [9] found a four rooted median nerve with three lateral and one medial root. Venieratos et al [10] reported a communicating branch between musculcutaneous nerve and median nerve, this branch after originating from muculocutaneous nerve procceeds downwards and medially to join the median nerve in the lower third of arm. These workers [4], [6], [8] reported that extra roots of median nerve were present unilaterally.…”
Section: Discussionmentioning
confidence: 98%
“…Another variation is communication between musculocutaneous nerve and median nerve. Venieratos and Anangnostopoulou [16] believed it to be the most frequent variant of this nerve where some fibers of the lateral root of the median nerve run along with the musculocutaneous nerve and after travelling some distance, leave the latter to join the ultimate destination (the median nerve). Communication between musculocutaneous and median nerve has been reported to seen with an incidence varying between10%-33.3% Type II-Some fibres of lateral root of median nerve pass through musculocutaneous nerve and join the median nerve at different levels in the form of communicating ramus.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that neither the nerve nor its communicating branch pierced the coracobrachialis muscle which is according to type 3 of Venieratos classification. 4 Fregnani et al and Pacholczak et al has reported absence of musculocutaneous nerve in the literature. Parchand and Patil reported complete merging of musculocutaneous nerve into median nerve and branches from median nerve innervated the muscles of anterior compartment instead of musculocutaneous nerve as observed in our study.…”
Section: Discussionmentioning
confidence: 99%